Integrating Local Wisdom and Digital Literacy: The BAJI AMPE Poster Model for Anti-Bullying and Learning in Indonesian Primary Education - Baharuddin, Baharuddin (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study addresses two critical issues identified at UPT SPF SDN Mangkura V, Makassar-low mastery of poster concepts among Grade 4 students and a declining sense of safety caused by bullying. Although character education and digital literacy are mandated in the Merdeka Curriculum, limited models integrate these competencies with local cultural wisdom. To fill this gap, the study aimed to develop and implement the BAJI AMPE-Based Poster Model, an instructional innovation grounded in South Sulawesi values of baji ampe (good deeds, mutual respect, togetherness) and aligned with Tudang Sipulung principles. Using an action research design, the intervention was implemented with 27 Grade 4 students and consisted of three phases: (1) Awareness mini-research and group discussions on bullying; (2) Solution Co-Designing collaborative development of digital posters using Chromebooks and Canva with embedded local language elements; and (3) Action and Sharing presentation, school-wide and social media dissemination, and reflective journaling supported by formative assessment. The results show that 24 students (89%) achieved full mastery of poster concepts, while 3 students (11%) demonstrated partial mastery. School-climate data also indicate a 34.14% increase in students’ perceived safety from bullying. The findings demonstrate that a culturally grounded, student-centered, and technology-supported learning intervention can simultaneously strengthen cognitive understanding and improve students’ sense of safety. The study contributes a low-cost, replicable instructional model for primary schools seeking to cultivate 21st-century competencies and advance the Pancasila Student Profile.